PEMETAAN GAMPONG SEMBUANG DAN PERENCANAAN PRASARANA GAMPONG SEMBUANG KECAMATAN SERBAJADI KABUPATEN ACEH TIMUR - Eka Mutia; Muhammad Zacky Ardhyan; Lely Masthura; Obed Haposan Sitompul (Fakultas Teknik, Universitas Samudra, 2023)
The completeness of the Gampong administration is something that must be done to achieve administrative order. The community service activities carried out in Gampong Sembuang which is located in the Lokop sub-district of East Aceh district aim to obtain the Gampong Sembuang Mosque Design, the Keuchik Office Design, and the Gampong Sembuang Map. The method used for the design activities of the Gampong Semburan Mosque and the Keuchik Office Design was to go directly to the field to obtain exact land size and shape data, while for Village Mapping activities the assistance was assisted using the Google Earth application and the student version of ArcGIS. The results of the community service activities were in the form of a poster of the Village Map, the design of the Gampong Mosque, and the Office of the Gampong Keuchik which were handed over to the Keuchik of Sembuang Gampong.